Magnetic conjugacy as observed at the apex of field lines: GEOS-1 and -2 results - Gendrin, Roger (1987)
P(論文) This report is the written version of an invited review presented at the NAGATA Symposium on Geomagnetically Conjugate Studies which was held during the 19th SCAR General Assembly. It deals with the relationships which exist between phenomena occurring at the apex of field lines, as detected by the European spacecraft GEOS-1 and -2,and those occurring at their foot prints, as observed by ground-based, balloons and rockets (GBR) techniques. Such simultaneous observations have allowed to obtain a more quantitative description of already known phenomena and to discover some new ones. The following topics are discussed in the paper : generation and propagation characteristics of ion cyclotron waves (ICW) in multi-component plasmas, quasi-linear interaction between VLF hiss and energetic electrons, cold plasma behaviour in the equatorial plasmasphere and its relationship with the global magnetospheric convection, existence of small-scale intense field-aligned currents (FAC). departmental bulletin paper